2010
DOI: 10.4314/ajnt.v1i1.58816
|View full text |Cite
|
Sign up to set email alerts
|

Post Transplant Diabetes Mellitus in Ahmed Gasim Kidney Transplant Center, Sudan

Abstract: Introduction: New onset post transplant diabetes mellitus (PTDM) is a common complication of kidney transplantation with a negative impact on patient and graft survival. Non-white ethnicity is a well known risk factor for PTDM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 21 publications
1
1
0
Order By: Relevance
“…The results of the present study concur with a retrospective study of 221 Sudanese patients who received live donor kidney transplantation in Ahmed Gasim Kidney Transplant Center between December 2001 and December 2007, in which the reported 12-month cumulative incidence of PTDM in the transplant population was 17.6% [ 9 ]. Similarly, in a study in Japan, where 127 post-transplant patients were followed up, the incidence rate of PTDM was 15.1% in Japanese kidney transplant recipients [ 16 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The results of the present study concur with a retrospective study of 221 Sudanese patients who received live donor kidney transplantation in Ahmed Gasim Kidney Transplant Center between December 2001 and December 2007, in which the reported 12-month cumulative incidence of PTDM in the transplant population was 17.6% [ 9 ]. Similarly, in a study in Japan, where 127 post-transplant patients were followed up, the incidence rate of PTDM was 15.1% in Japanese kidney transplant recipients [ 16 ].…”
Section: Discussionsupporting
confidence: 90%
“…A number of large studies compared the cumulative incidence of PTDM in tacrolimus and cyclosporinetreated patients and showed that tacrolimus was associated with a higher relative risk of PTDM when compared to cyclosporine [8][9][10]. Studies have reported an incidence of 4.7% in patients receiving cyclosporine versus 11.5% of those on tacrolimus-based immunosuppression, post-renal transplant [10].…”
Section: Need For Studymentioning
confidence: 99%